(4x+2)=(6x-30)

Simple and best practice solution for (4x+2)=(6x-30) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4x+2)=(6x-30) equation:


Simplifying
(4x + 2) = (6x + -30)

Reorder the terms:
(2 + 4x) = (6x + -30)

Remove parenthesis around (2 + 4x)
2 + 4x = (6x + -30)

Reorder the terms:
2 + 4x = (-30 + 6x)

Remove parenthesis around (-30 + 6x)
2 + 4x = -30 + 6x

Solving
2 + 4x = -30 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
2 + 4x + -6x = -30 + 6x + -6x

Combine like terms: 4x + -6x = -2x
2 + -2x = -30 + 6x + -6x

Combine like terms: 6x + -6x = 0
2 + -2x = -30 + 0
2 + -2x = -30

Add '-2' to each side of the equation.
2 + -2 + -2x = -30 + -2

Combine like terms: 2 + -2 = 0
0 + -2x = -30 + -2
-2x = -30 + -2

Combine like terms: -30 + -2 = -32
-2x = -32

Divide each side by '-2'.
x = 16

Simplifying
x = 16

See similar equations:

| 7a+4m+7= | | 6-x+2=-3 | | Y=21x+98 | | 6-6a=-6-5a+5 | | 7/3x+2/5= | | 2x=77 | | y+.8=.6(y+4) | | 3+2x+5=-17 | | 3(2t+2)= | | y=0.2x^3-5 | | -2xb= | | 2m+9=90 | | f(x)=-4cos(x) | | 6y-16=90 | | f(-x)=7x^2+3x-8 | | 518=vot-16t^2 | | 5x+7=x-17 | | 518=vot-16t | | 6x-(2)=26 | | 5(x-2)=8x-x | | p=4x+450 | | 0.3X-1.8=-5.04 | | -10=3f+2f | | 14+7x-6-15x+5=5x+7-12x+5-12 | | S=c+xv | | 2y-4y=6 | | 29+4y-3=17y-14-5y | | (3x-6)=(x+10) | | 5k+12+k=x+28 | | 13f+6=-5 | | 2*(2a+3)=18 | | -9*2-3(-56+12*2)=78 |

Equations solver categories